British Medical Association and the National Health Service Bill (1946)
1946 1946 1940s 8 pages clerical facilities, the provision of premises specially built for the purpose, are obvious. Some disadvantages, particularly from the point of view of the public, are no less obvious. For example, patients will travel greater distances, they will suffer some loss of privacy, there may well be a loss of the personal touch. No details are given of the kind of health centre it is proposed to develop. The health centre outlined in the Coalition White Paper can be fairly described as an aggregation of doctors' consulting and waiting rooms, with common nursing and clerical help. This does not meet the real need. What general practitioners need, above all, is the provision of facilities for fuller diagnosis, with special emphasis on pathology and radiology. The extent to which such facilities can be made available in health centres should be a matter of widespread experimentation before the lines of central policy are laid down. 21. The building of Health Centres will take a considerable time. Pending their construction the effect of the Government's proposals will be not what it seeks, the encouragement of group medicine, but the opposite. The abolition of goodwill will of itself destroy the present basis of partnership agreements, breaking up partnerships into units of individual practitioners who may or may not reach arrangements between themselves. This may be still the case when health centres are in action. Further, no indication is given that the Government contemplates, in its proposed arrangements, the status of "assistant." It appears that all general practitioners in the proposed service, whatever their age or experience, will practise as individuals. 22. If the duty to provide and maintain health centres is vested in local health authorities, it will be difficult to avoid the present limitations of local facilities to the residents of particular local government areas. It is doubtful whether a health centre provided and maintained by one local authority would be available to the residents in an adjacent local authority area. This would involve some restriction of the patient's free choice of doctor. As has been urged in an earlier paragraph, the ownership and administration of health centres should be vested in the regional body. 23. The following statement was made by the Minister of Health in the House of Commons on Thursday, December 6th, 1945: "1. The Government have not yet finally decided upon the proposals which they will be submitting to Parliament for a National Health Service. 2. They believe, however, that it will be incompatible with the provision of an efficient service that the future exchange of medical practices and the creation of new practices within that service should be left entirely unregulated, and that no effective steps should be taken to secure a proper distribution of doctors to fit the public need. 3. I appreciate that intervention in this field, in whatever form it may take, will probably have the effect of preventing the sale and purchase of the practices of doctors taking part in the new service and the Government therefore think it right to give warning of this probability at once and in advance of the formulation of their full proposals. 4. At the same time and in order to allay the natural anxieties of doctors already in practice, or coming into practice from the Forces or elsewhere, the Government wish to make it clear that there will be an appropriate measure of compensation to doctors in respect of loss of capital values directly caused by the new arrangements. It is intended that discussions should be undertaken immediately with the profession's representatives with regard to the steps to be taken to give effect to this decision." 24. The Government proposes to control the distribution of doctors and recognizes that such control will destroy the selling value of practices wholly or partly in the public service. The method of control will be to require new entrants to the public service to apply to the local executive council, which will pass the application on to the Central Committee on the Distribution of Medical Practices, the decision as to whether the applicant is to be allowed to practise in a particular area being made by the latter body. A central point of Government policy is the decision to achieve a better distribution of general practitioners by control. In the view of the profession such control is unnecessary and undesirable. An examination of the figures of the distribution of doctors in relation to population before the war shows, admittedly, an irregularity of distribution and some under-doctored areas. Generally speaking these areas are not local government areas; usually they are pockets and not complete towns or counties. But it must not be thought that such irregularity merely exhibits a preference on the part of doctors for wealthier areas. For example, the ratio of general practitioners to population shows that Barrow-in-Furness, Darlington and Macclesfield were in the years before the war provided with more doctors per thousand of population than Richmond, Rugby or Winchester. When the age and health record of the local doctors has been examined, as it has been by the Central Medical War Committee during the war, it has been commonly shown that apparently over-doctored areas are, in fact, no better served in terms of medical man-power than apparently less well-doctored areas. 25. The introduction of National Health Insurance was briskly followed by a more even distribution of 6 292/847/4/40